PENGARUH SISTEM INFORMASI AKUNTANSI, PEGENDALIAN INTERNAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR ADIARTHA UDIANA - Margareta Ni Kadek Swahyuni; K. Fridagustina Adnantara (Journal Research of Accounting, 2020)
The purpose of this study was to determine the effect of accounting information systems (X1) on employee performance (Y) at PT. BPR Adiartha Udiana, the influence of internal control (X2) on employee performance (Y) at PT. BPR Adiartha Udiana, the effect of work motivation (X3) on employee performance (Y) at PT. BPR Adiartha Udiana, and the effect of simultaneous accounting information system (X1), internal control (X2), work motivation (X3) on employee performance (Y) at PT. BPR Adiartha Udiana. The population in this study amounted to 46 people. The data analysis technique used is multiple linear regression analysis. The conclusion obtained is that the accounting information system (X1) partially has no influence on employee performance (Y) at PT. BPR Adiartha Udiana indicated at a significance value of 0.729 greater than 0.05. Internal control (X2) and work motivation (X3) partially have a positive influence on employee performance (Y) at PT. BPR Adiartha Udiana, this can be seen at a significance value of 0.041 and 0.016 smaller than 0.05. Accounting information system (X1), internal control (X2) and work motivation (X3) have a simultaneous effect on employee performance (Y) at PT. BPR Adiartha Udiana indicated at a significance value of 0,000 smaller than 0,005. The magnitude of the influence of accounting information systems, internal control and work motivation on employee performance at PT. BPR Adiartha Udiana amounted to 67.7% and the remaining 33.3% was influenced by other variables not examined in this study.